Self Disclosure in the Interpersonal Communication Process of Establishing Friends with Benefits (FWB) Relationship Agreement on Telegram - Monica Gabriela (Communication Science Department - Petra Christian University, 2023)
The phenomenon of Friends with Benefits (FWB) romantic relationships developed in Western countries that embrace freedom began to develop also in Indonesia with globalization and supported by technological developments. In contrast to dating relationships bound by feelings of love and commitment, the parties in a Friends with Benefits (FWB) relationship are only bound by an agreement on the benefits of sexual activity, without any feelings or c ommitments. The Telegram application has the advantage of large-scale community or group chat features. This research found a unique group community looking for Friends with Benefits (FWB) relationship partners in Indonesia. This research focuses on self -disclosure or self -disclosure in the process of interpersonal communication in personal chatting by prospective partners to establish a Friends with Benefits (FWB) relationship agreement on Telegram. This qualitative research approach with a case study method found four informants who are members of a particular community looking for Friends with Benefits (FWB) couples on Telegram and are establishing interpersonal communication to establish a Friends with Benefits (FWB) relationship agreement. The research findings show that the exploration of sexual desire accelerates the course of self -disclosure; women pursue the depth of personal profiles, men pursue the depth of intimacy, and self -disclosure measures a sense of security and comfort, which can determine the